Recidivism and Barriers to Reintegration: A Field Experiment Encouraging Use of Reentry Support - Marco Castillo; Sera Linardi; Ragan Petrie (CESifo GmbH, 2024)
Many previously incarcerated individuals are rearrested following release from prison. We investigate whether encouragement to use reentry support services reduces rearrest. Field experiment participants are offered a monetary incentive to complete different dosages of visits, either three or five, to a support service provider. The incentive groups increased visits, and one extra visit reduces rearrests three years after study enrollment by six percentage points. The results are driven by Black participants who are more likely to take up treatment and benefit the most from visits. The study speaks to the importance of considering first-stage heterogeneity and heterogeneous treatment effects.
Keywords: K42; C93; 330; recidivism; reentry support services; dosage effects; field experiment